PENGARUH HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KAMAR DI GRAND ROYAL DENAI HOTEL BUKITTINGGI - Wira Novrilla Ananda Putri (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
ABSTRACT This research aims to find out how much the Price and Location Influence on Room Purchase Decisions atathe Grand Royal Denai Hotel Bukittinggi. In making purchasing decisions there are five stages that are considered by constumers before making a purchase decision, recognizing needs, seeking information, evaluating alternatives, purchasing decisions, and post-purchase behavior. And any factors that are considered by guests when making purchasing decisions. These factors are products, places, promotions, prices, people, processes, and physical evidance. Sample in this study amounted to 90 samples with of incidental sampling. Data was collected using a questionnaire with a Likert scale. Analysis technique used in this study is descriptive analysis using multiple linear regression analysis. The results of this study have significantly influenced the price of the decision to purchase rooms at the Grand Royal Denai Hotel Bukittinggi with a score of 51.2% while the rest (48.8%) is influenced by other factors. Keywords: Price, Location, Purchase Decision